Antimicrobial Activity of Gentamicin-Loaded Biocomposites Synthesized through Inverse Vulcanization from Soybean and Sunflower Oils - Farioli, Ana Sofia (2024)
Cross-linked polymers synthesized through inverse vulcanization of unsaturated vegetable oils (biopolymers) were used as matrices for incorporating gentamicin (GEN) to form a biocomposite that can amplify GEN antimicrobial activity against Pseudomonas aeruginosa. Two different biopolymers were synthesized using soybean (PSB) and sunflower (PSF) oils by inverse vulcanization cross-linked with sulfur in a 1:1 weight ratio. The study involves the synthesis and characterization of these biopolymers using FTIR and SEM as well as measurements of density and hydrophobicity. The results reveal the formation of biopolymers, wherein triglyceride molecules undergo cross-linking with sulfur chains through a reaction with the unsaturated groups present in the oil. Additionally, both polymers exhibit a porous structure and display hydrophobic behavior (contact angle higher than 120°). The biopolymers swell more in GEN solution (PSB 127.7% and PSF 174.4%) than in pure water (PSB 88.7% and PSF 109.1%), likely due to hydrophobic interactions. The kinetics of GEN sorption and release within the biopolymer matrices were investigated. The antibacterial efficacy of the resulting biocomposite was observed through the analysis of inhibition growth halos and the assessment of P. aeruginosa viability. A notable enhancement of the growth inhibition halo of GEN (13.1 ± 1.1 mm) compared to encapsulated GEN (PSF-GEN 21.1 ± 1.3 and PSB-GEN 21.45 ± 1.0 mm) is observed. Also, significant bactericidal activity is observed in PSF-GEN and PSB-GEN as a reduction in the number of colonies (CFU/mL), more than 2 log10 compared to control, PSF, and PSB, highlighting the potential of these biopolymers as effective carriers for gentamicin in combating bacterial infections.